The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000180118
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Epi-LASIK for the Correction of High Myopia and Myopic Astigmatism after More than 1 Year

Abstract: Purpose: To present the clinical results of epi-LASIK in a high myopia and myopic astigmatic population followed for more than 1 year. Methods: This retrospective study comprised 67 eyes of 52 patients who underwent epi-LASIK for the correction of high myopia and myopic astigmatism. Epi-LASIK was performed with an automatically rotational epikeratome (KM-5000D, Wuxi Kangming Medical Device Corp., Wuxi, China) and the MEL80 (Carl Zeiss Meditec, Jena, Germany) excimer laser. The postoperative symptom, epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It can be determined whether the treatment was on axis or off axis and whether too much or too little effect was achieved. The Alpins method has been used by several authors to analyze the astigmatic changes induced with different surgical and nonsurgical options, including relaxing incisions, 34,35 excimer laser refractive surgery, [36][37][38][39][40] cataract surgery, 41 vitrectomy, 42 orthokeratology. 43 The information obtained with this analysis can help optimize the selection of toric IOL power and define predictive factors for a good visual outcome after cataract surgery with implantation of these IOLs.…”
Section: Resultsmentioning
confidence: 99%
“…It can be determined whether the treatment was on axis or off axis and whether too much or too little effect was achieved. The Alpins method has been used by several authors to analyze the astigmatic changes induced with different surgical and nonsurgical options, including relaxing incisions, 34,35 excimer laser refractive surgery, [36][37][38][39][40] cataract surgery, 41 vitrectomy, 42 orthokeratology. 43 The information obtained with this analysis can help optimize the selection of toric IOL power and define predictive factors for a good visual outcome after cataract surgery with implantation of these IOLs.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate whether the treatment was on axis or off axis and whether the achieved effect is too great or too little. The Alpins method has been used to analyze astigmatic changes induced by many surgical and nonsurgical options, such as relaxing incisions, 25,26 excimer laser refractive surgery, [27][28][29][30][31] cataract surgery, 32 vitrectomy, 33 and orthokeratology. 34 However, to our knowledge, the method has not been used to analyze astigmatic changes after ICRS implantation in eyes with an ectatic cornea.…”
mentioning
confidence: 99%
“…[6][7][8][9]19 In addition, the procedure was associated with reduced postoperative pain and corneal haze formation. 1,20,21 However, other reports and our previous results showed that epi-LASIK offered somewhat slower reepithelialization, improved pain relief, and better visual recovery in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Therefore, it has been reported that patients treated with epi-LASIK have less pain and show faster recovery compared with patients treated using other procedures, and it is known that epi-LASIK is safe and efficient in correction of low to moderate myopia and myopic astigmatism. [6][7][8][9] However, previous studies reported that, compared with patients undergoing other procedures, epi-LASIK patients had similar or less pain only during the immediate postoperative period. [10][11][12] Other reports and our previous studies found that patients suffered more postoperative pain after the epi-LASIK procedure than did patients undergoing photorefractive keratectomy (PRK) or laser-assisted subepithelial keratectomy (LASEK) in which epithelial flap was made after application of 20% (vol/vol) ethanol and was repositioned.…”
mentioning
confidence: 99%